Phylogenetics of the tribe Phalacropsyllini (Siphonaptera: Ctenophthalmidae: Neopsyllinae) based on molecular and morphological evidence - Acosta, Roxana; Morrone, Juan J. (Zootaxa, 2013)
Six genera of the tribe Phalacropsyllini were analysed based on molecular (18S rDNA and 28S rDNA) and morphological characters, using maximum parsimony analyses and Bayesian inference. The results support the paraphyly of the tribe Phalacropsyllini, as shown in a previous study based only on molecular characters. Three main clades were identified: one includes the genera Neopsylla, Epitedia, Catallagia, and Delotelis; another includes Phalacropsylla and Strepsylla; and a third one includes only Meringis. In order to propose a phylogenetic classification we recognize three tribes, transferring Epitedia, Catallagia and Delotelis to Neopsyllini; keeping Phalacropsyllini only for Phalacropsylla and Strepsylla; and proposing the new tribe Meringini for Meringis.